Recent advances in wheel-rail RCF and wear testing - Sundar Shrestha; Maksym Spiryagin; Esteban Bernal; Qing Wu; Colin Cole (Friction)
Abstract The wear and rolling contact fatigue (RCF) testing approaches for wheels and rails have been reviewed and evaluated in this study. The study points out the advantages and limitations of the existing approaches. The broad analysis revealed that scaled laboratory-based wear testing is widely applied. However, it is necessary to predetermine the input parameters and observing parameters for scaled wear testing for three reasons: first, to emulate the real-world scenarios as closely as possible; second, to postprocess the results received from the scaled testing and transfer them into real practice at full scale; third, to present the results in a legible/appropriate format. Therefore, most of the important parameters required for wear testing have been discussed with fundamental and systematic explanations provided. Additionally, the transition of the parameters from the real-world into the test domain is explained. This study also elaborates on the challenges of the RCF and wear testing processes and concludes by providing major considerations toward successful testing.